Desempenho, qualidades de carcaça e de carne em suínos large white de linhagens distintas - Campos, Dúnia Ibrahim (2008)
Twenty-two castrated male pigs individually housed were used to compare two different genetics lineages (A and B) derived from Large White breed, submitted to different tools of genetic selection, considering: growth performance, intestinal morphometry, carcass and pork quality. In each of the two lineages, they were analised for: (1) Performance: weight, total feed intake, feed efficiency, carcass yield, viscera weight and intestinal morphometry; (2) Carcass quality: Water holding capacity, drip loss, color, intramuscular fat, muscular fibers morphometry (LD and SM muscles), sensorial analysis, and leptin (obese) gen. There were no statistical difference (p>0.05) between studied lineages, showing standard of rearing conditions. Divergent tools in genetic selection didn t influence performance growth, carcass and pork quality. Pork form both lineage were considered of great quality by consumer s test.